Pembelajaran Literasi Anak Melalui Pendekatan Kecakapan Hidup Di Rumah Pintar Bangjo Semarang - Ningrum, Sekar Fitria; Fakhruddin, Fakhruddin (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to explore the implementation of children's literacy learning through a life skills approach at Rumah Pintar Bangjo Semarang. Children's literacy is one of the important aspects in the development of early childhood education, which includes not only the ability to read and write, but also critical and creative understanding of information. The life skills approach is relevant in this context because it can integrate literacy learning with practical skills that are useful in everyday life. The research method used was qualitative with a case study approach. Data were collected through observation, interviews and documentation of activities at Rumah Pintar Bangjo, which were then analyzed descriptively. The results showed that the application of the life skills approach in children's literacy learning at Rumah Pintar Bangjo succeeded in increasing children's interest in reading, social skills and ability to solve problems. In addition, learning based on real-life contexts also enriches children's insights into the world around them. The conclusion of this study is that the life skills approach can be an effective method in supporting children's literacy learning, which not only focuses on academic aspects, but also the development of social and emotional skills that are important for children's lives.